DISSENTERS AND DISSIDENTS: RELIGIOUS CONSCIENTIOUS OBJECTORS UNDER YUGOSLAV MILITARY CRIMINAL LAW 19451991: JERETICI I DISIDENTI: VERNICI PRIGOVARAČI SAVESTI I JUGOSLOVENSKO VOJNO KRIVIČNO PRAVO OD 1945. DO 1991. - Božić, Marko D (Pravni zapisi, 2023)
The paper presents results of a research focusing on a four decades’ struggle for legal recognition of the right to conscientious objection in Socialist Yugoslavia. Without a pretense to evaluate it, the paper aspires to describe and explain the evolution of Yugoslav Military Criminal Law by examining its distinctive historical causes and inner logic. Methodologically, the study relies on normative analysis of relevant legal sources that have been either understudied or simply disregarded. It analyzes especially the 1989 Amendment to the Military Service Obligation Act that introduced the right to conscientious objection into the Yugoslav socialist legal system, as well as related archival materials, newspaper reports and other written accounts depicting the political background of the 1989 legal reform. The study sheds light on socialist secularism and questions the common perception of the Yugoslav People’s Army as a conservative institution unwilling to compromise. It also contributes to a broader theoretical discussion on the ambiguous nature of conscientious objection as a right and/or a privilege.
Keywords: Right to conscientious objection; Socialist Yugoslavia; Yugoslav People’s Army; religious conscientious objector; Protestant dissenting groups; Slovenian Peace Movement